Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 1-9 - Cumulative Review - Page 763: 66



Work Step by Step

$(5x-6)^{2}$ =$(5x-6)(5x-6)$ =$5x(5x-6)-6(5x-6)$ =$25x^{2}-30x-30x+36$ =$25x^{2}-60x+36$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.